Creating public value : strategic management in government - Moore, Mark H., 1947- (Cambridge, Mass. : Harvard University Press, 1995)
A seminal figure in the field of public management, Mark Moore presents his summation of fifteen years of research, observation, and teaching about what public sector executives should do to improve the performance of public enterprises. Useful for both practicing public executives and those who teach them, this book explicates some of the richest of several hundred cases used at Harvard's Kennedy School and illuminates their broader lessons for government managers.
Moore addresses four questions that have long bedeviled public administration: What should citizens and their representatives expect and demand from public executives? What sources can public managers consult to learn what is valuable for them to produce? How should public managers cope with inconsistent and fickle political mandates? How can public managers find room to innovate?
1. Managerial Imagination -- Pt. I. Envisioning Public Value. 2. Defining Public Value. 3. Organizational Strategy in the Public Sector -- Pt. II. Building Support and Legitimacy. 4. Mobilizing Support, Legitimacy, and Coproduction: The Functions of Political Management. 5. Advocacy, Negotiation, and Leadership: The Techniques of Political Management -- Pt. III. Delivering Public Value. 6. Reengineering Public Sector Production: The Function of Operational Management. 7. Implementing Strategy: The Techniques of Operational Management. Conclusion: Acting for a Divided, Uncertain Society.
Includes bibliographical references and index.
Keywords: Civil service ethics; Government executives; Public administration; Strategic planning